Low temperature magnetic phase diagram of the cubic non-Fermi liquid system Celn(3-x)Sn(x) - Pedrazzini, P. (2004)
Fil: Pedrazzini, P. Comisión Nacional de Energía Atómica. Instituto Balseiro. Laboratorio de Bajas Temperaturas; Argentina